Etude de la propriété inhibitrice du compose Nferrocenylmethyl-4-aminoacetophenone vis-à-vis de la corrosion de l'acier XC52 en milieu H2SO4 - إلياس, لبيهيات; سعد, فائزة; أسامة, كيم (University of El-Oued, 2022)
"Abstract: Calculating the thickness of the corrosion formed on a carbon steel surface can give an idea of the evolution of this phenomenon as well as the deterioration of the latter during an event that can cause the rupture of the chains of industrial production. In the first part of this work, a theoretical explanation of the electrochemical techniques used to determine the corrosion rate of an iron oxide film from the reaction between protons in water in which sulfuric acid is dissolved at a concentration of M0.5 and a metal cation Fe+. The aim of this work is to study the corrosion inhibiting power of the organic compound Nferrocenylmethyl-4-aminoacetophenone, and based on the parabolic circuit model which helps us to determine the iron oxide film formed in the absence and in the presence of different concentrations of inhibitors with immersion times up to 240 minutes; The results obtained indicate that the inhibitory capacity increases with the concentration of N-ferrocenylmethyl-4-aminoacetophenone to reach the maximum efficiency around the concentration of 30ppm. The Tafel right shift is interpreted as Nferrocenylmethyl-4-aminoacetophenone which has cathodic inhibition after the corrosion potential turns to negative values with the shift of mV250." "الملخص: يمكن أن يعطي حساب سمك التآكل المتكون على سطح من الصلب الكربوني فكرة عن تطور هذه الظاهرة وكذلك تدهور األخيرة أثناء سير الشيء الذي يمكن أن يتسبب في تمزق سالسل اإلنتاج الصناعي. في الجزء األول من هذا العمل تم إجراء شرح نظري للتقنيات الكهروكيميائية المستخدمة لتحديد نسبة التآكل لفيلم من أكسيد الحديد من التفاعل بين البروتونات .Fe+ الموجودة في الماء الذي يذوب فيه حامض الكبريتيك بتركيزM0.5والكاتيون المعدني. الهدف من هذا العمل هو دراسة قوة تثبيط التآكل للمركب العضوي N-ferrocenylmethyl-4-aminoacetophenone ,و انطالقا من نموذج الدائرة المكافئ الذي يساعدنا في تحديد فيلم أكسيد الحديد المتكون في غياب وفي وجود تركيزات مختلفة من المثبطات مع أوقات غمر تصل إلى 240دقيقة ؛ النتائج التي تم الحصول عليها تشير إلى أن القدرة المثبطة تزداد مع تركيز N-ferrocenylmethyl-4-aminoacetophenone للوصول إلى أقصى قدر من الكفاءة حول تركيز 30جزء في المليون. اإلزاحة الى اليمين من Tafel تفسر على أن N-ferrocenylmethyl-4-aminoacetophenone الذي لديه تثبيط كاثودي بعد احتمال التآكل يتحول إلى قيم سالبة مع إزاحة mV250. "
مذكرة ماستر تخصص هندسة طرائق
Keywords: Keywords: Corrosion, Electrochemical impedance spectrum, polarization curve; الكلمات المفتاحية: التآكل ، طيف الممانعة الكهروكيميائية ، منحنى االستقطاب